2018
DOI: 10.1186/s12974-018-1115-7
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ αβ T cell infiltration into the leptomeninges of lumbar dorsal roots contributes to the transition from acute to chronic mechanical allodynia after adult rat tibial nerve injuries

Abstract: Background: Antigen-specific and MHCII-restricted CD4+ αβ T cells have been shown or suggested to play an important role in the transition from acute to chronic mechanical allodynia after peripheral nerve injuries. However, it is still largely unknown where these T cells infiltrate along the somatosensory pathways transmitting mechanical allodynia to initiate the development of chronic mechanical allodynia after nerve injuries. Therefore, the purpose of this study was to ascertain the definite neuroimmune inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 57 publications
5
58
0
Order By: Relevance
“…We performed von Frey filament tests to assess the response to mechanical stimulation using two methods: the first response method and the up-down method. In comparison to wild-type mice, TNX −/− male mice showed significantly lower thresholds of nociceptive responses, as assessed by either the lowest force required to elicit a withdrawal reflex (the first response method; wild-type male: 1.07 ± 0.10 g (n = 14) versus TNX −/− male: 0.14 ± 0.04 g (n = 13), P < 0.001, one-way ANOVA with post hoc Bonferroni test F (3,45) = 15.15, P < 0.001, Fig. 2a) or the 50% withdrawal threshold (the up-down method; wild-type male: 0.87 ± 0.09 g (n = 11) versus TNX −/− male: 0.46 ± 0.07 g (n = 9), P < 0.05, one-way ANOVA with post hoc Bonferroni test F (3,38) = 11.94, P < 0.0001, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed von Frey filament tests to assess the response to mechanical stimulation using two methods: the first response method and the up-down method. In comparison to wild-type mice, TNX −/− male mice showed significantly lower thresholds of nociceptive responses, as assessed by either the lowest force required to elicit a withdrawal reflex (the first response method; wild-type male: 1.07 ± 0.10 g (n = 14) versus TNX −/− male: 0.14 ± 0.04 g (n = 13), P < 0.001, one-way ANOVA with post hoc Bonferroni test F (3,45) = 15.15, P < 0.001, Fig. 2a) or the 50% withdrawal threshold (the up-down method; wild-type male: 0.87 ± 0.09 g (n = 11) versus TNX −/− male: 0.46 ± 0.07 g (n = 9), P < 0.05, one-way ANOVA with post hoc Bonferroni test F (3,38) = 11.94, P < 0.0001, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A relationship between leptomeninges and neuropathic pain has been reported. Selective infiltration of CD4+ αβ T cells into the dorsal root leptomeninges of somatosensory pathways induces the mechanical allodynia after peripheral nerve injury 45 . Taken together, the data suggest that TNX-mediated regulation of the construction and function of the leptomeninges may induce mechanical allodynia, although this possibility requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical excision of lumbar lymph nodes and cervical lymph nodes prior to experimental allergic encephalomyelitis (EAE) induction, reduces EAE severity by interfering with immunological priming [5], supports the concept that the CNS-draining lymph nodes are essential in the induction and severity of neuroinflammation versus non-draining lymph nodes [11]. Moreover, interestingly, lumbar lymph node-originated Lymphocytes at dorsal root leptomeninges has an important role in the development of chronic mechanical allodynia after tibial nerve injuries in rat, whereas lymphadenectomy of cervical and other CNS non-draining lymph node did not show any significant effect [6]. This implies that the nearest CNS-draining lymph node has the most potent immuneboosting capabilities against injury.…”
Section: Introductionmentioning
confidence: 55%
“…Tissue-draining lymph nodes, which could serve as sinks for cellular and solute transportation, are essential active-site for generating immune responses during inflammations, as well as in maintaining tolerance to minimize tissue damage [1][2][3][4]. The central nervous system-draining lymph nodes are thus likely vital for the balancing of protective versus harmful immune responses in experimental models of neuroinflammation [5][6][7][8]; however, surprisingly identification and functional characterization of CNS-draining lymph nodes during spinal cord injury have remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have reported that CXCL10 promotes the entry of peripheral immune cells into the spinal cord (24,25). On the other hand, some studies and our recent report have shown that T cell infiltration of the dorsal horn may contribute to the onset of neuropathic and inflammatory hyperalgesia (11,12,26,27). However, it is unknown whether these processes contribute to hyperalgesia following peripheral nerve injury.…”
Section: Introductionmentioning
confidence: 89%